2018
DOI: 10.1080/1359432x.2018.1541886
|View full text |Cite
|
Sign up to set email alerts
|

Systematically reviewing remote e-workers’ well-being at work: a multidimensional approach

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
469
5
28

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 447 publications
(631 citation statements)
references
References 128 publications
26
469
5
28
Order By: Relevance
“…Fourth, our results showed that people who worked from home or did not work during the pandemic presented greater problems of coexistence than key workers who have continued to work in person. Previous research (Charalampous, Grant, Tramontano, & Michailidis, 2019;Gajendran & Harrison, 2007) indicates that con icts and disturbances between household members will increase as working from home practices are extended, as it blurs the boundaries between workspace and home life. In fact, almost 50% of employees who have been working from home during the COVID-19 crisis reported additional con icts with their family members and stated that they bother them more frequently (Baert, Lippens, Moens, Sterkens, & Weytjens, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, our results showed that people who worked from home or did not work during the pandemic presented greater problems of coexistence than key workers who have continued to work in person. Previous research (Charalampous, Grant, Tramontano, & Michailidis, 2019;Gajendran & Harrison, 2007) indicates that con icts and disturbances between household members will increase as working from home practices are extended, as it blurs the boundaries between workspace and home life. In fact, almost 50% of employees who have been working from home during the COVID-19 crisis reported additional con icts with their family members and stated that they bother them more frequently (Baert, Lippens, Moens, Sterkens, & Weytjens, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The interview guideline was developed by the author team in two iterative circles and was informed by research in the fields of connectivity (Dery et al, 2014;Kolb et al, 2012), remote work (Charalampous et al, 2019;Koslowski et al, 2019) and technology disconnection (Cai et al, 2020). The interview guideline consisted of questions around if and how the enforced working from home situation has changed the way our participants use technology to a) complete their work tasks, b) collaborate with their peers and superiors and c) interact with their clients.…”
Section: Data Collectionmentioning
confidence: 99%
“…Acharya [32] studied remote workers in virtual teams in the area of administration and economy in three cities in India. Charalampous et al [33] and Donnelly and Johns [34] researched the areas of psychology, business and administration. The first analyzed 63 quantitative, qualitative and mixed studies, finding social isolation to be a negative factor.…”
Section: G Related Workmentioning
confidence: 99%